ANALISIS INDEKS MATURITY SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK (SPBE) DINAS INFORMASI DAN KOMUNIKASI KABUPATEN SERAM BAGIAN BARAT - Sarnita Wolio; Jusuf Madubun; Stanislaus Kostka Ohoiwutun (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2025)
This study aims to determine and analyze the level of maturity of SPBE and recommendations for improving aspects for SPBE implementation based on the evaluation results in the West Seram Regency Government. This study focuses on the SPBE of the SBB Regency Government, where the focus of this research is carried out at the SBB Regency Communication and Information Service. Data observation is carried out on the achievement of SPBE implementation in the SBB Regency Government.The data analysis technique used is the calculation to determine the assessment of the level of maturity and weight and determine the aggregate index value of the maturity level value for each SPBE implementation indicator. Measurement of each level of maturity is given a value of level 1 to 5. Weights are given to domains and aspects according to different levels of importance. The weight of each domain and aspect can be seen in the SPBE maturity level criteria, namely; Process Capability Maturity Level and Service Capability Maturity Level. The results of the study concluded that the results of the SPBE maturity level evaluation through the monitoring and evaluation guidelines of PermenPANRB Number 59 in 2020, the West Seram Regency Government obtained an index value of 1.86 with the predicate "Sufficient". The West Seram Regency Government has weaknesses in all aspects of SPBE implementation, both in terms of internal policies, governance, Management and SPBE services. It has used several applications developed by the central government or developed within its own scope, but the service features of the applications built need to be developed in optimizing public services in West Seram Regency.